2023
DOI: 10.1001/jamapediatrics.2022.6172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intranasal Corticosteroid on Quality of Life and Local Microbiome in Young Children With Chronic Rhinosinusitis

Abstract: ImportanceIntranasal corticosteroids (INCs) remain the first-line treatment of chronic rhinosinusitis (CRS) in both adults and children, despite the lack of evidence regarding their efficacy in the pediatric population. Similarly, their effect on the sinonasal microbiome has not been well documented.ObjectiveTo assess the clinical, immunological, and microbiological effects of 12 weeks of an INC in young children with CRS.Design, Setting, and ParticipantsThis open-label randomized clinical trial was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…Furthermore, the authors demonstrated that the increase in bacterial diversity was correlated with the decrease in clinical symptoms, suggesting a possible causal relationship. Therefore, they conclude by stating that treatment with an INC improved the quality of life of children with CRS [20]. In another paper, Liu et al evaluated the impact of topical budesonide and saline irrigations on the postsurgical sinonasal microbiota by examining the nasal and sinus swabs of twenty-eight controls and fourteen patients with refractory CRSwNP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors demonstrated that the increase in bacterial diversity was correlated with the decrease in clinical symptoms, suggesting a possible causal relationship. Therefore, they conclude by stating that treatment with an INC improved the quality of life of children with CRS [20]. In another paper, Liu et al evaluated the impact of topical budesonide and saline irrigations on the postsurgical sinonasal microbiota by examining the nasal and sinus swabs of twenty-eight controls and fourteen patients with refractory CRSwNP.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the role of topical steroids, while Liu et al found no significant changes in the nasal microbiome when treating patients with topical budesonide, Latek et al demonstrated that treatment with topical mometasone had a significant effect on improving sinonasal biodiversity and improving the QoL of young patients [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Streptobacillus and Staphylococcus abundance were consistently correlated with age in both adenoid‐ and sinus‐derived samples. Finally, an open‐label randomized controlled trial assessing pediatric CRS with intranasal corticosteroid treatment leads to a greater increase in nasopharyngeal microbiome richness and a larger decrease in nasal Type 3 Innate Lymphoid Cell abundance 26 . These collective findings suggest pediatric CRS has distinct characteristics and behaviors when compared to adult CRS 27 …”
Section: Discussionmentioning
confidence: 98%
“…However, there was an objective increase in the abundance and diversity of the nasal microbiome in posttransplant patients, which authors attributed the symptom improvements to. In a group of pediatric CRS patients, treatment with intranasal corticosteroids for 12 weeks was found to be associated with a greater increase in nasopharyngeal microbiome biodiversity, with a concomitant decrease in nasal innate lymphoid cell abundance and improvement in quality of life scores [2,3,42].…”
Section: The Role Of the Nasal Microbiome In Chronic Rhinosinusitismentioning
confidence: 99%